IL-6/JAK/STAT3 Signaling in Breast Cancer Metastasis: Biology and Treatment - Manore, Sara G.; Doheny, Daniel L.; Wong, Grace L.; Lo, Hui-Wen (Frontiers in Oncology, 2022)
Breast cancer is the most commonly diagnosed cancer in women. Metastasis is the primary cause of mortality for breast cancer patients. Multiple mechanisms underlie breast cancer metastatic dissemination, including the interleukin-6 (IL-6)-mediated signaling pathway. IL-6 is a pleiotropic cytokine that plays an important role in multiple physiological processes including cell proliferation, immune surveillance, acute inflammation, metabolism, and bone remodeling. IL-6 binds to the IL-6 receptor (IL-6Rα) which subsequently binds to the glycoprotein 130 (gp130) receptor creating a signal transducing hexameric receptor complex. Janus kinases (JAKs) are recruited and activated; activated JAKs, in turn, phosphorylate signal transducer and activator of transcription 3 (STAT3) for activation, leading to gene regulation. Constitutively active IL-6/JAK/STAT3 signaling drives cancer cell proliferation and invasiveness while suppressing apoptosis, and STAT3 enhances IL-6 signaling to promote a vicious inflammatory loop. Aberrant expression of IL-6 occurs in multiple cancer types and is associated with poor clinical prognosis and metastasis. In breast cancer, the IL-6 pathway is frequently activated, which can promote breast cancer metastasis while simultaneously suppressing the anti-tumor immune response. Given these important roles in human cancers, multiple components of the IL-6 pathway are promising targets for cancer therapeutics and are currently being evaluated preclinically and clinically for breast cancer. This review covers the current biological understanding of the IL-6 signaling pathway and its impact on breast cancer metastasis, as well as, therapeutic interventions that target components of the IL-6 pathway including: IL-6, IL-6Rα, gp130 receptor, JAKs, and STAT3.